Optimization of Gelling Agent of Sunflower (Helianthus annuus) Seed Oil Gel and Its Stability and Activity Test In Vitro as Sunscreen - Abdul Karim Zulkarnain; Feela Faridhotu; Ifthary Naqsya PR (Majalah Obat Tradisional, 2022)
Excessive ultraviolet (UV) radiation from the sun can harm human skin, such as skin erythema or sunburn, premature aging of the skin, darker skin discoloration, and damage to skin cells. Skin protection, like sunscreen, is needed to prevent the negative effects of UV rays. This study aims to evaluate the optimum formula, the physical properties, and the activity of a sunscreen gel preparation of sunflower seed oil in vitro. The method in this study was optimization with Design Expert version 10 of the carbopol gelling agent and sodium carboxymethyl cellulose. The optimum formula obtained was tested for its physical properties and activity as a sunscreen in vitro with a spectrophotometer.  The results showed that the physical properties of the optimum formula were good, and stable during storage, pH, spreadability, adhesion, and viscosity were close to predictions, and the in vitro SPF test obtained a value of 15.60.